Determination Of Liquefaction Sediment Volume In Balaroa VillageUsing The Geoelectric Resistance Type Method - Asgar; M. Rusydi; Rustan Efendi; Moh. Dahlan Th Musa; Badaruddin (LPPM Universitas Tadulako, 2022)
Introduction: Research has been carried out titled